Analysis of Relationship between Leadership and Employee Performance at Manufactur Company in Indoenesia - Puspa Liza, Ghazali; Juliana, Arifin; Nik Hazimi, Mohammed Foziah; Dedi, Iskamto; Abu Talib, Bon; Jenita, Jasman; Mahbubah, Srimulatsih; Putra Budi, Ansori (2021)
The research objective is to determine the influence of leadership on employee performance at Utama Prima Karya Ltd. Pekanbaru, Indonesia . This research was a quantitative method. The data analyzed used SPSS 26. The result of the t-test showed that the t-value is 5.339, bigger than t table 1.99714. So H0 is rejected, and Ha is accepted. It concluded that there is a positive and significant influence of leadership variables on employee performance . The coefficient of determination (R2) is 0.305. It means that the leadership influence on employee performance is 30.5%, while the remaining 69.5% influenced by other variables not included in this study.